Analysis of adversity quotient of nursing students in Macao: A cross-section and correlation study - Xin Wang; Ming Liu; Stephen Tee; Hongxia Dai (Elsevier, 2021)
Objectives: To investigate the adversity quotient (AQ) of Macao undergraduate nursing students and analyse its influencing factors. Methods: A cross-section design was used, and a convenience sample of nursing students (n = 158 valid) was selected from a tertiary institute in Macao. In addition to demographic questions, the Chinese versions of the Adversity Quotient Scale, the Emotional Intelligence (EI) Scale, the Simplified Coping Style Questionnaire and the Parenting Styles Scale were used to assess the students' characteristics. Results: The average AQ score of the students was 116.72 ± 11.39. AQ scores were negatively correlated with coping-negative, and maternal style (excessive interference, excessive protection) (r = −0.332, P < 0.001; r = −0.167, P = 0.036). Coping-negative entered the regression equation (F = 19.154, P < 0.001). The female nursing students had higher scores in ownership dimension of AQ than their male counterparts (31.98 ± 3.26 vs. 29.21 ± 3.08, t = −4.442, P < 0.001). Conclusions: The average AQ scores of Macao undergraduate nursing students were moderate. The female nursing students are more likely to attribute the cause of adversity to themselves, and specific psychosocial and cultural issues may be at play. There is a necessity for Macao nursing students to improve their ability to overcome setbacks. Special attention should be paid to the cultivation of students' positive coping styles.